Choosing among β-blockers in heart failure patients according to β-receptors' location and functions in the cardiopulmonary system. (June 2020) - Sinagra, Gianfranco; Corrà, Ugo; Contini, Mauro; Magrì, Damiano; Paolillo, Stefania; Perrone Filardi, Pasquale; Sciomer, Susanna; Badagliacca, Roberto; Agostoni, Piergiuseppe
Graphical abstract: Abstract: Several large clinical trials showed a favorable effect of β-blocker treatment in patients with chronic heart failure (HF) as regards overall mortality, cardiovascular mortality, and hospitalizations. Indeed, the use of β-blockers is strongly recommended by current international guidelines, and it remains a cornerstone in the pharmacological treatment of HF. Although different types of β-blockers are currently approved for HF therapy, possible criteria to choose the best β-blocking agent according to HF patients' characteristics and to β-receptors' location and functions in the cardiopulmonary system are still lacking. In such a context, a growing body of literature shows remarkable differences between β-blocker types (β1-selective blockers versus β1-β2 blockers) with respect to alveolar-capillary gas diffusion and chemoreceptor response in HF patients, both factors able to impact on quality of life and, most likely, on prognosis. This review suggests an original algorithm for choosing among the currently available β-blocking agents based on the knowledge of cardiopulmonary pathophysiology. Particularly, starting from lung physiology and from some experimental models, it focuses on the mechanisms underlying lung mechanics, chemoreceptors, and alveolar-capillary unit impairment in HF. This paper also remarks the significant benefit deriving from the correct use of the different β-blockers in HF patients through a brief overview of the most important clinical trials.